2007
DOI: 10.1111/j.1523-1739.2007.00777.x
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal Variation in the Prevalence and Intensity of Chytrid (Batrachochytrium dendrobatidis) Infection in Eastern Australia

Abstract: Chytridiomycosis is a recently emerged, infectious skin disease of amphibians that has been linked directly to mass mortalities, population declines, and species extinctions worldwide. An understanding of the factors that limit the distribution and abundance of Batrachochytrium dendrobatidis (the etiological agent of chytridiomycosis) is urgently required. We conducted disease surveys at 31 lowland sites distributed north-south along 2315 km of the Australian east coast that encompassed 20.8 degrees of latitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
134
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(148 citation statements)
references
References 44 publications
12
134
2
Order By: Relevance
“…In amphibians, conditions in the larval environment, such as density of conspecifics, can determine size at metamorphosis; larger amphibian body size is associated with increased overwinter survival, earlier time to first reproduction, and increased fecundity (Berven, 1990; Earl & Whiteman, 2015; Semlitsch & Wilbur, 1988). For some amphibian species, the size of individuals has been linked to higher likelihood of Bd infection (Kriger, Pereoglou, & Hero, 2007; Searle et al., 2011) and survival after infection (Carey et al., 2006; Garner et al., 2009). Hosts of larger sizes may be more likely to be infected because of their increased ability to mount immune responses and survive.…”
Section: Introductionmentioning
confidence: 99%
“…In amphibians, conditions in the larval environment, such as density of conspecifics, can determine size at metamorphosis; larger amphibian body size is associated with increased overwinter survival, earlier time to first reproduction, and increased fecundity (Berven, 1990; Earl & Whiteman, 2015; Semlitsch & Wilbur, 1988). For some amphibian species, the size of individuals has been linked to higher likelihood of Bd infection (Kriger, Pereoglou, & Hero, 2007; Searle et al., 2011) and survival after infection (Carey et al., 2006; Garner et al., 2009). Hosts of larger sizes may be more likely to be infected because of their increased ability to mount immune responses and survive.…”
Section: Introductionmentioning
confidence: 99%
“…Variations in natural history, life history, behavioral, and immunologic traits among species can strongly affect the development and outcome of Bd infection (Voyles et al 2011). In addition, intraspecific variation in ecology (e.g., Puschendorf et al 2009), geography (e.g., Kriger et al 2007), and season (e.g., Lannoo et al 2011) can also influence infection prevalence, infection intensity, and host mortality. Batrachochytrium dendrobatidis infections are generally thought to be most intense in cool, humid habitats (e.g., Woodhams et al 2005) and in species that aggregate when threatened by dehydration (Longo et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, bioclimatic modeling predicts that the fungus is more likely to inhabit wetter regions (Ron, 2005), and recent field studies confirm this prediction. Kriger et al (2007) found that both the prevalence and intensity of B. dendrobatidis infections in eastern Australia increase significantly in regions with high rainfall. Whereas chytrid infections were detected at all 17 sites that had received over 33 mm of rainfall in the 30 days prior to sampling, infections were detected at only half of the 14 sites that received less than 33 mm of rainfall.…”
mentioning
confidence: 99%
“…Whereas chytrid infections were detected at all 17 sites that had received over 33 mm of rainfall in the 30 days prior to sampling, infections were detected at only half of the 14 sites that received less than 33 mm of rainfall. Kriger and Hero (2007a) demonstrated that B. dendrobatidis is largely restricted to wet microhabitats. Whereas 38.8% of 402 frogs breeding in permanent water bodies were infected with B. dendrobatidis, only one of 117 frogs breeding in ephemeral water bodies or in leaf litter was infected.…”
mentioning
confidence: 99%
See 1 more Smart Citation